2015
DOI: 10.1177/0040517515612359
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-electronic behaviors investigation of knitted heating fabrics based on silver plating compound yarns

Abstract: In this paper, three kinds of knitted heating fabrics (KHFs) were designed and fabricated by using silver plating compound yarns (SPCYs) and polyester staple fiber spun yarns (PSFSYs), and thermo-electric properties of KHFs and SPCYs were investigated by performing a series of experiments. Experimental results showed, with increasing ageing time and ageing temperature, the breaking strength of PSFSYs and SPCYs had nearly not changed, but resistances of SPCYs increased markedly. After performing 264 hours agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…A thermoplastic polyurethane (TPU) film (thickness = 150 µm; Ceylon 3095) was applied on top of the prepared SHE fabric via thermal transfer (165 • C for 15 s under a load of 10 kg) (Figure 4, step 2 ). Two sections of high-stretch fabric with the same dimensions were prepared separately, where TPU was also applied to one surface via thermal transfer (Figure 4, step 3 ). The two fabric sections were attached to the top and bottom of the SHE by thermally bonding the TPU-coated fabric surfaces (Figure 4, step 4 ).…”
Section: Fabrication Of Ptc-sht and Ntc-shtmentioning
confidence: 99%
See 3 more Smart Citations
“…A thermoplastic polyurethane (TPU) film (thickness = 150 µm; Ceylon 3095) was applied on top of the prepared SHE fabric via thermal transfer (165 • C for 15 s under a load of 10 kg) (Figure 4, step 2 ). Two sections of high-stretch fabric with the same dimensions were prepared separately, where TPU was also applied to one surface via thermal transfer (Figure 4, step 3 ). The two fabric sections were attached to the top and bottom of the SHE by thermally bonding the TPU-coated fabric surfaces (Figure 4, step 4 ).…”
Section: Fabrication Of Ptc-sht and Ntc-shtmentioning
confidence: 99%
“…The behavior of the PTC-SHT and NTC-SHT heating elements were compared based on the applied voltage, applied power, and heating temperature change under a constant voltage. 1 electrode patterning and screen printing, 2 TPU film bonding, 3 External textile preparation (TPU film bonding), 4 Bonding of inner and outer textiles.…”
Section: Fabrication Of Ptc-sht and Ntc-shtmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying the behavior of a silver-coated polyester yarn embedded in three different knit structures showed that the maximum equilibrium surface temperature of heated knit fabrics is strongly correlated with the energy consumption density. Furthermore, the maximum equilibrium surface temperature can be influenced by the knitting method, as the electrical resistance of some structures seems to remain more stable than others during the heating process [164].…”
Section: Silver Coated Yarnsmentioning
confidence: 99%